Comparison of molecular and culture method in diagnosis of prosthetic joint infection. Issue 1 (2nd April 2013) - Rak, Mitja; Barlič‐Maganja, Darja; Kavčič, Martina; Trebše, Rihard; Cőr, Andrej
Abstract Diagnosis of prosthetic joint infection with culture technique can be problematic since the causative agent(s) are not possible to cultivate in all cases. Molecular methods had been evaluated in many studies but their inclusion in routine diagnostics is still controversial. The purpose of our prospective study was to compare the diagnostic accuracy of broad‐range (BR)‐PCR and culture technique. Intraoperative samples of periprosthetic tissue were retrieved in 67 patients undergoing revision arthroplasty. Samples were analyzed with culture technique, immunohistochemistry and BR 16S rRNA gene PCR. Bacteria in PCR‐positive samples were identified using two different methods: direct sequencing of PCR products and specific TaqMan assays. In 63 cases, full concordance was found between BR‐PCR and culture technique. Specific TaqMan assays failed to identify bacteria in four culture‐ and BR‐PCR‐positive cases and therefore had a lower sensitivity in comparison with BR‐PCR. Molecular methods detected bacteria with the same accuracy as culture; however, identification of bacteria was inferior to culture. Further development of species‐recognition techniques is required to improve identification of causative microorganisms.